(3cJGH Sdje Hf bjS GdgdGdjs - (3eLghds ((3gGOj Hf YHGS GdWHGWHGFjs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3bGd MOKfG CHh WGdH eMeO Hf UHjM Hf QLGA HOeTb SfI CQHY hKdGKjf hKdKeGFg bGd CNHQfj CHh YeQh YUeI Hf CHj YUeI GdHNGQj bGd MOKfG CHh HcQ CMeO Hf GdefPQ Hf CMeO GdUfYGfj (B..s
(3BNQgG (B:s
... (3hYfg Yf Sdje Hf bjS bGd SeYJ SdeGf GdaGQSj jbhd (B: (3Ef YdjG HGH aJMg Gddg ef ONdg cGf eDefG hef NQL efg cGf cGaQG (B. (3Je GdcJGHs
(3JHUQI GdYfhGf (B:s
(3CMGOjK Sdje Hf bjSs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdMOjK hGdeUWdMs